Aplikasi Pengenalan Organ Tubuh Manusia Berbasis Android Menggunakan App Inventor Di Jurusan Biologi Universitas Papua - Hendra Muttu; Kristia Ky Yuliawan; Parmahadi Rantelinggi (Faculty of Computer Science, University of Jember, 2021)
Learning is a communication process between lecturers and students. Communication will not run without the help of means of conveying messages or media that support learning productivity. In modern times like today, more and more people, especially students, have Android smartphones as the main equipment for daily communication. In the biology department at the University of Papua at this time, learning still uses the lecture dictates as a teaching aid. If the lecture dictates are lost or wet due to waterlogging, the student must spend funds to buy a new lecture dictates. To overcome this problem, new alternatives are needed in learning aids. For this reason, android-based applications for the introduction of human organs can make it easier for lecturers to deliver the learning process material for the introduction of human organs so that learning outcomes for students become easy and interesting. This research was conducted by creating an application using the app inventor service. This application contains material about the description of the introduction of human organs. For testing the application testing uses the black box method and survey methods for application users so that the level of user satisfaction with the application can be seen.